Effect of nitrogen sources and concentration on bioflocculant inoculum - Nur Aquilla Fatihah, Mohd Sopian (2023)
Bioflocculation fish farming of Catfish or “Ikan Patin” (Iridescent Shark) has been proved channeled great demand due to its ability of water control management. Yet, there is still lack of research has been done particularly on the inoculum stage in biofloc system to improve the fish production. This study was conducted to identify the best nitrogen sources and concentration on the production of bioflocculant inoculum. The influence of various nitrogen sources was studied (urea and commercial ikan patin fish meal) and various concentration of nitrogen sources (0.01, 0.03, 0.05, 0.07, and 0.09). The bacterial growth and the ammonia removal. The bacterial growth analysis was analyzed using cell dry weight and optical density while ammonia test was used to determine the ammonia removal in bioflocculation inoculum. The highest bacterial growth (0.0421 g) was measured at concentration 0.05 g/L for urea. Meanwhile, 0.0073 g was the highest bacterial growth recorded by using fish meal (0.09 g/L) as nitrogen sources. Similarly, the same results recorded for optical density since both of analysis were done to determine bacterial growth after day 5 and 8. The highest removal of ammonia was at 88% at 0.05 g/L urea’s concentration while 77.5% removal when using 0.09 g/L fish meal as the nitrogen sources. These results are useful prior fermentation process since it tells at what days should the process start and the best concentration of nitrogen sources and concentration to use in order to have a better production of biofloc.